EXTREME LASER RADIATION: PHYSICS AND FUNDAMENTAL APPLICATIONS : Influence of induced colour centres on the frequency – angular spectrum of a light bullet of mid-IR radiation in lithium fluoride. (31st March 2017) - Chekalin, S V; Kompanets, V O; Dormidonov, A E; Kandidov, V P
Abstract: The influence of the occurrence of a structure consisting of long-lived colour centres, formed in an LiF crystal upon filamentation of femtosecond mid-IR radiation, on the supercontinuum characteristics is investigated. With an increase in the number of incident pulses, the length and transverse size of the structure of colour centres induced in LiF increase, and the supercontinuum spectrum in the short-wavelength region is markedly transformed due to the occurrence of the waveguide propagation regime, absorption, and scattering of radiation from the newly formed structure of colour centres. Under these conditions, the intensity of the anti-Stokes wing decreases by two orders of magnitude after several tens of pulses. Spectral components arise in the visible range, the angular divergence of which increases with increasing wavelength.